Oral ciprofloxacin activity against ceftriaxone-resistant Escherichia coli in an in vitro bladder infection model. (7th December 2022) - Abbott, Iain J; van Gorp, Elke; Cottingham, Hugh; Macesic, Nenad; Wallis, Steven C; Roberts, Jason A; Meletiadis, Joseph; Peleg, Anton Y
Abstract: Objectives: Pharmacodynamic profiling of oral ciprofloxacin dosing for urinary tract infections caused by ceftriaxone-resistant Escherichia coli isolates with ciprofloxacin MIC ≥ 0.25 mg/L. Background: Urine-specific breakpoints for ciprofloxacin do not exist. However, high urinary concentrations may promote efficacy in isolates with low-level resistance. Methods: Ceftriaxone-resistant E. coli urinary isolates were screened for ciprofloxacin susceptibility. Fifteen representative strains were selected and tested using a dynamic bladder infection model. Oral ciprofloxacin dosing was simulated over 3 days (250 mg daily, 500 mg daily, 250 mg 12 hourly, 500 mg 12 hourly and 750 mg 12 hourly). The model was run for 96 h. Primary endpoint was change in bacterial density at 72 h. Secondary endpoints were follow-up change in bacterial density at 96 h and area-under-bacterial-kill-curve. Bacterial response was related to exposure (AUC0–24 /MIC; C max /MIC). PTA was determined using Monte-Carlo simulation. Results: Ninety-three clinical isolates demonstrated a trimodal ciprofloxacin MIC distribution (modal MICs at 0.016, 0.25 and 32 mg/L). Fifteen selected clinical isolates (ciprofloxacin MIC 0.25–512 mg/L) had a broad range of quinolone-resistance genes. Following ciprofloxacin exposure, E. coli ATCC 25922 (MIC 0.008 mg/L) was killed in all dosing experiments. Six isolates (MIC ≥ 16 mg/L) regrew in all experiments. Remaining isolates (MIC 0.25–8 mg/L) regrew variably after an initial period of killing, depending on simulated ciprofloxacin dose. A >95% PTA, using AUC0–24 /MIC targets, supported 250 mg 12 hourly for susceptible isolates (MIC ≤ 0.25 mg/L). For isolates with MIC ≤ 1 mg/L, 750 mg 12 hourly promoted 3 log10 kill at the end of treatment (72 h), 1 log10 kill at follow-up (96 h) and 90% maximal activity (AUBKC0–96 ). Conclusions: Bladder infection modelling supports oral ciprofloxacin activity against E. coli with low-level resistance (ciprofloxacin MIC ≤ 1 mg/L) when using high dose therapy (750 mg 12 hourly).